Implementing the Extractive Industries Transparency Initiative : Applying Early Lessons From the Field - World Bank (Washington, DC : World Bank, 2012)
This report provides information about some of the common issues that have arisen and lessons that have been learned in countries implementing Extractive Industries Transparency Initiative (EITI), and to which the World Bank's EITI team has been exposed through its involvement in supporting EITI implementation. These are "early" or preliminary lessons, because implementation processes are evolving in most countries that have committed to EITI. Some countries have produced EITI reports, but analysis of these reports is still at an early stage. It is hoped that this report will stimulate further discussion on implementation choices that face government policy makers; civil society groups; oil, gas, and mining companies; and donor agencies involved in the initiative.